Performance improvement, culture, and regimes: Evidence from the Ontario Municipal Performance Measurement Program, 2000-2012 - Charbonneau, Étienne; Bromberg, Daniel E.; Henderson, Alexander C. (The International journal of public sector management, 2015)
Purpose - The purpose of this paper is to better understand the performance improvement outcomes that result from the interaction of a performance regime and its context over more than a decade. Design/methodology/approach - A series of partial free disposable hull analyses are performed to graph variations in performance for 13 services in 444 municipalities in one province for over a decade. Findings - There are few examples of mass service improvements over time. This holds even for relative bottom performers, as they do not catch up to average municipalities over time. However, there is also little proof of service deterioration during the same period. Research limitations/implications - A limitation results from the high churning rate of the indicators. The relevance of refining indicators based on feedback from practitioners should not be dismissed, even if it makes the task of proving performance improvement more difficult. It is possible that the overall quality of services on the ground improved, or stayed stable despite diminishing costs, without stable indicators to capture that reality. Practical implications - Not all arrangements incentives and structures of - performance regimes - are equally fruitful for one level of government to steer a multitude of other governments on the generalized path to improved performance. Social implications - With the insight that was not available to public managers putting together these performance regimes in the beginning of the 2000s, the authors offer a proposition: mass performance improvement is not to be expected out of intelligence regime. It neither levels nor improves performance for all (Knutssonet al. , 2012). Though there are benefits to such a regime, a general rise in performance across all participants is not one of them. Originality/value - Performance improvements are assessed under difficult, yet common characteristics in the public sector: budgetary realities where there are trade-offs between many services, locally set priorities, no clear definition of what constitutes a good level of performance, and changes in the indicators over time.